O violino solo na música contemporânea para além da partitura: a ética na relação compositor-intérprete - Ayran Nicodemo Oliveira (2023)
The practice of Performance invites us to complexity. To interpret it is to assume an existential condition regarding music. The composer's relationship with the performer is one of the aspects of this complexity and, when it comes to contemporary music in which the composer is present in life, we can investigate dynamic aspects of this interaction, made possible by the meeting of both. Initially, a historical context of the solo violin genre will be presented, which was chosen for the investigation, in order to characterize this type of formation in the different periods of music history and in the works of Brazilian composers. Then, based on the characteristics of the composer-performer relationship indicated by Brandino in his Dissertação (2012), I propose to approach this relationship through an existential-phenomenological point of view, which raises an ethical question in the encounter between both, having the historical context as one of the existential constituents of the composer-performer relationship. This approach allows expanding the research and practice of Performance through the foundations of existential philosophy and phenomenological method. In order to do that, we will use the qualitative method proposed by the philosopher Merleau-Ponty. The objective is to look at the phenomenon of the construction of an unprecedented solo repertoire in a way that allows the two artists to make this meeting ethic, later indicating in the final considerations which skills can be stimulated and developed during the learning of these professionals so that, at each meeting , the human and social dimension of artistic creation is inaugurated, emphasizing the need to understand that both exist in the world. The ontological being, according to the philosopher Martin Heidegger, is the one that exists in the world, its essence is actually its existence. Hence, being-there (Dasein) is a faculty of the entity that is ontological, that gives meaning to its life and to the phenomena it experiences.